A robust protocol for directed aryl sulfotransferase evolution toward the carbohydrate building block GlcNAc. Issue 5 (22nd January 2018) - Islam, Shohana; Mate, Diana M.; Martínez, Ronny; Jakob, Felix; Schwaneberg, Ulrich
Abstract: Bacterial aryl sulfotransferases (AST) utilize p ‐nitrophenylsulfate ( p NPS) as a phenolic donor to sulfurylate typically a phenolic acceptor. Interest in aryl sulfotransferases is growing because of their broad variety of acceptors and cost‐effective sulfuryl‐donors. For instance, aryl sulfotransferase A (ASTA) from Desulfitobacterium hafniense was recently reported to sulfurylated ‐glucose. In this study, a directed evolution protocol was developed and validated for aryl sulfotransferase B (ASTB). Thereby the well‐known p NPS quantification system was advanced to operate efficiently as a continuous screening system in 96‐well MTP format with a true coefficient of variation of 14.3%. A random mutagenesis library (SeSaM library) of ASTB was screened (1, 760 clones) to improve sulfurylation of the carbohydrate building block N‐acetylglucosamine (GlcNAc). The beneficial variant ASTB‐V1 (Val579Asp) showed an up to 3.4‐fold increased specific activity toward GlcNAc when compared to ASTB‐WT. HPLC‐ and MS‐analysis confirmed ASTB‐V1's increased GlcNAc monosulfurylation (2.4‐fold increased product formation) representing the validation of the first successful directed evolution round of an AST for a saccharide substrate. Abstract : A directed aryl sulfotransferase evolution protocol was successfully validated for enhancing the specific activity toward a monosaccharide, N‐acetylglucosamine (GlcNAc). A random mutagenesis library of aryl sulfotransferase B (ASTB) from Desulfitobacteroium hafniense was generated using SeSaM method and screened via advanced and optimized p NPS‐based screening system as an example for small sugar molecule, GlcNAc. The identified "best" variant (ASTB‐V1) was characterized in terms of specific activity and product determination using HPLC/MS.